Linked data technology and linked open data in academic libraries in Nigeria: level of integration, challenges and potential solution (2023)
The emergence of Linked Data and Linked Open Data technologies in the library and information service environment has altered the platform of bibliographic standards and models. Despite the perception that Linked Data technology will soon be the standard for creating metadata for information resources management in libraries, there tends to be very low level of adoption of this emerging technology in the developing economy. This study examined the level of integration, challenges and potential solutions in the adoption of Linked Data (LD) and (LOD) in academic libraries in Nigeria. Survey research design was adopted for the study. This consists of Questionnaire instrument distributed to Library and Information professionals in Nigeria. Seventy-one responses were received across seventeen higher institutions in Nigeria. The study exposed that most of the academic libraries in Nigeria have not started the implementation of linked data standards at all. The major challenges in the adoption of LD in Nigeria are lack of in-depth knowledge on the potential values and procedural activities of LD and LOD technology amongst librarians and information managers, and poor infrastructure, coupled with the concerns that the system could be hacked. The study identified the need for investment of both social and financial capital into LD technology. Librarians and other key stakeholders should be exposed to trainings and events on LD application. Such trainings can be pioneered by the host institutions